Understanding of political tasks in the cognitive process of socio-political being - Traverse, T. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The article considers the an understanding the psychological characteristics of political activity by modern actor, in particular the features of polycontextual reclaiming the specific socio-political situation. Socio-political facts are largely the products of social construction. The content of solved political problems is not one and the same for people of different historical epochs and historical conditions. The application of new forms of thinking significantly changes the character of policy subject matter as a activity. At present assume that the object of policy remains the same. With all these, even well-known structured problems are changeable, their semantic content varies depending on the situation, involved parties and others its components. In the process of policymaking (as most "reasonable" in the context of socio-historical perspective) just values, and thus irrational criterion appears basis of their decision, not an intellectual justification. Such a cognitive activity depends on the degree of involvement to a policy from forming in actors process of solving political problems and understanding in the context of political thinking. It is about an understanding as the criteria process stage and the result of political thinking, political an understanding of the relationship management and knowledge about them.